Macroecologia dos modos reprodutivos em anuros da Mata Atlântica: gradientes de diversidade reprodutiva e influência de fatores ambientais - Gimenez, Paula Letícia de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Os anfíbios anuros exibem a maior variedade de modos reprodutivos (MR) dentre os tetrápodes. A Mata Atlântica (MA) é um importante hotspot para a conservação da biodiversidade mundial onde a diversidade de anuros é uma das maiores do mundo. Apesar disso, estudos biogeográficos documentando gradientes de modos reprodutivos ainda são escassos e pontuais nesta área. Assim, objetivamos por descrever os padrões geográficos de diversidade reprodutiva dos anuros da Mata Atlântica. Confeccionamos mapas de riqueza de modos reprodutivos baseados em mapas de distribuição de anuros e informações sobre os modos de reprodução disponíveis na literatura. Para tal, sobrepomos mapas de 252 espécies com modos reprodutivos de ovos aquáticos e mapas de 101 espécies com modos reprodutivos de ovos terrestres/arborícolas, separadamente, em um sistema de 469 grids de ~50 km de resolução ao longo da Mata Atlântica. Observamos que, independentemente do tipo de especialização, a maior diversidade reprodutiva localiza-se na região costeira da Mata Atlântica, enquanto o menor número de modos reprodutivos na região interiorana da MA do sudeste e sul do Brasil é mais pronunciada para a diversidade de ovos não-aquáticos. As análises de correlação dos preditores ambientais e o gradiente de diversidade reprodutiva mostraram que a riqueza de MR aquáticos pode ser descrita por combinações gerais de clima, relevo e vegetação, enquanto os MR não-aquáticos são melhores descritos por variáveis específicas de sazonalidade de temperatura e pela presença de florestas ombrófilas e relevos acidentados. Os estudos de conservação destas espécies e o monitoramento florestal são de extrema importância para identificar a partir de que ponto uma variação ambiental pode ser mais provável de levar uma espécie à extinção.

Anuran amphibians exhibit the widest variety of reproductive modes (RM) among the tetrapods. The Atlantic Forest (AF) is an important hotspot for the conservation of biological diversity, of which the anuran diversity is one of the highest in the world. Yet, biogeographic studies documenting RM gradients are still scarce in the AF. Thus, the aim of this Dissertation is to describe the geographical patterns of reproductive diversity of AF anurans, separately for RM of aquatic eggs and non-aquatic eggs. We built RM richness maps based on anuran distribution maps and RM information available in the literature. We then overlaid maps of 252 species with RM having aquatic eggs and maps of 101 species with RM having land/arboreal eggs separately in a system of 469 grids of ~50 km resolution along the AF. Irrespective of the type of RM specialization, we found the greatest reproductive diversity in the coastal region of AF, probably associated with the higher amounts of rainfall and humidity provided by the ombrophiles forests of this region. However, the lower number of RM in inland regions of the AF of southeastern and southern Brazil is more pronounced for the diversity of non-aquatic eggs. At this region, semi-deciduous forests are characterized by a warmer, drier climatic regime with seasonality of the rain/heat and cold/dry seasons well delimited over the years, which presumably limit the presence of more specialized RM of non-aquatic eggs, which depend on a more humid microenvironment for their development. Correlative analyses showed that the richness of aquatic RM can be described by general combinations of climate, topography and vegetation, whereas non-aquatic RM are better described by specific variables of temperature seasonality, amount of ombrophiles forests and rough topography. Thus, the monitoring of these environmental variables, the conservation of humid forests, and the detection of trends of climate change (e.g., due to current activities that cause environmental impact) are important in conservation studies for these species, mainly to identify threshold values that an environmental variation may be more likely to lead a species to extinction.
Macroecology of reproductive modes in anurans of the Atlantic Forest: gradients of reproductive diversity and influence of environmental factors
Keywords: Anfíbios Neotropicais; Biogeografia; Diversidade reprodutiva; Hotspot de biodiversidade; Neotropical amphibians; Biogeography; Reproductive diversity; Biodiversity hotspot